Pemanfaatan Internet pada Mahasiswa STIKes Panti Rapih dalam Menciptakan Institusi Pendidikan yang Damai dan Inklusif - Scholastica Fina Aryu Puspasari (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: A tranquillity and inclusive institution is everyone's hope as stated in the Sustainable Development Goals (SDGs). In era of industrial revolution 4.0, there were actually various problems due to technological advancements including cybercrime, human trafficking, violence, hoaxes, abuse, which ultimately created institutions that weren’t conducive. Indonesia is the second highest country in the case of cybercrime with a total of 90 million. Most cases of technological abuse occur in adolescence, whereas adolescents are the nation's successors who’re expected to be able to use technology wisely. Objective: To describe the technology utilization among students at STIKes Panti Rapih. Methods: Qualitative study with univariate analysis to find out the technology utilization in daily activity. 112 students of Nursing Diploma Degree Study Program that chosen randomly using the lottery system. Results: 55.4% of students rarely validated the correctness of information and 43.6% didn’t read information until completion, 40% had flaming, 21.8% harassment, 50.9% denigration and trickery, 12,7% impersonation, 32.8% outing, 35.5% exclusion, and 5.5% cyberstalking. Conclusion: Most students do not engage in meaningful misuse of the internet but almost half have not filtering information properly. Keywords: utilization, technology, students